Natural ventilation design of a terrace house - Mohd Azril Mahazan (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
This project has been carried out and two models terrace house were built. One house with natural ventilation design and one another house model that has no natural ventilation design.